FAKTOR YANG MEMPENGARUHI NYERI PUNGGUNG BAWAH PADA USIA DEWASA MADYA DI JAKARTA DAN SEKITARNYA TAHUN 2020 - Tashya Anggraeni Sinaga (2021)
Low back pain is a global health problem that affects productivity of those who suffered from it. Middle-aged adults are forced to be highly productive at the same time their lower back starts to age. Therefore, middle-aged adults are at risk of having low back pain. Individual, occupational and psychosocial risk factors have been studied but are still showing different results and only a few studies has been conducted regarding these factors among middle-aged adults especially in Jakarta. This study was conducted to determine factors associated with low back pain in middle-aged adults in Jakarta and its surroundings. This cross sectional study used convenience sampling method with a total of 321 samples. Data were collected through questionnaire and analyzed with logistic regression. The result shows that the prevalence of low back pain in the last 12 months were 50.4%. There was a significant relationship between female gender, smoking habit and sitting while working for more than 4 hours with low back pain. It can be concluded from this study that female gender (OR 2.24, CI 1.36-3.7), Smoking habit (OR 2.76 CI 1.4-5.4) and working while sitting for more than 4 hours (OR 1.9 CI 1.15-3.23) were the risk factors associated with low back pain among middle-aged adults.